4‐Oxo‐(E)‐2‐hexenal produced by Heteroptera induces permanent locomotive impairment in crickets that correlates with free thiol depletion. Issue 1 (14th April 2015) - Noge, Koji; Becerra, Judith X.
Abstract : Heteropterans produce 2‐alkenals and 4‐keto‐2‐alkenals that function as defense substances or pheromones. However, in spite of advances in heteropteran chemistry, it is still unclear how these compounds affect insect physiology. We found that exposure to 4‐oxo‐( E )‐2‐hexenal (OHE) induced permanent paralysis and death in crickets, an experimental model. The depletion of free thiols in leg tissues of OHE‐treated crickets and the in vitro adduct formation of OHE with a thiol compound suggest that covalent binding of OHE to biologically active thiols is a potential cause affecting crickets' locomotion. Abstract : Heteropterans produce 4‐keto‐2‐aldehydes that function as anti‐predatory defenses. 4‐Oxo‐( E )‐2‐hexenal (OHE) induces permanent locomotive impairments in crickets. Covalent binding of OHE to biologically active thiols is a potential cause affecting insect locomotion.